HYDRAULIC CONCRETE COMPOSITION AND PROPERTIES CONTROL SYSTEM - Pshinko, O. M.; Krasnyuk, A. V.; Hromova, O. V. (Science and Transport Progress, 2015)
Purpose. Scientific work aims at the development and testing of information system to meet the challenges of concrete composition design and control (for railway structures and buildings) based on the physico-analytical method algorithm for hydraulic concrete composition calculation. Methodology. The proposed algorithm of hydraulic concrete composition calculation is based on the physicochemical mechanics and in particular on the rheology of elastic–viscous–plastic bodies. The system of canonical equations consists of the equations for concrete strength, absolute volume, concrete mix consistency as well as the equation for optimal concrete saturation with aggregates while minimizing cement content. The joint solution of these four equations related to composition allows determining for the materials the concrete composition of required strength, concrete workability with minimum cement content. The procedure for calculation of hydraulic concrete composition according to the physico-analytical method consists of two parts: 1) physical, which is laboratory testing of concrete mix components in different concrete compositions; 2) analytical, which represents the calculation algorithm for concrete compositions equivalent in concrete strength and workability that comply with the specific conditions of concrete placing. Findings. To solve the problem of designing the concrete composition with the desired properties for railway structures and buildings it was proposed to use the information technology in the form of a developed computer program whose algorithm includes the physico-analytical method for hydraulic concrete composition determination. Originality. The developed concrete composition design method takes into account the basic properties of raw materials, concrete mix and concrete, which are pre-determined. The distinctive feature of physico-analytical method is obtaining of a set of equivalent compositions with a certain concrete mix consistency and required concrete strength, which allows to optimize the concrete composition by any optimality criterion, depending on the operation conditions. Practical value. Using the developed method will expand its functionality when applied in the form of the composition calculation computer program for the construction and repair of surface and underwater structures. The use of physico-analytical method at production site will simultaneously solve the economic problems of construction and maintenance cost reduction, component saving and ensure obtaining the concrete with the set properties for specific operation conditions of transport engineering structures.